Functional and Phylogenetic Characterization of Bacteria in Bovine Rumen Using Fractionation of Ruminal Fluid - Hernández, Ruth; Chaib De Mares, Maryam; Jimenez, Hugo; Reyes, Alejandro; Caro-Quintero, Alejandro (Frontiers in Microbiology, 2022)
Cattle productivity depends on our ability to fully understand and manipulate the fermentation process of plant material that occurs in the bovine rumen, which ultimately leads to the improvement of animal health and increased productivity with a reduction in environmental impact. An essential step in this direction is the phylogenetic and functional characterization of the microbial species composing the ruminal microbiota. To address this challenge, we separated a ruminal fluid sample by size and density using a sucrose density gradient. We used the full sample and the smallest fraction (5%), allowing the enrichment of bacteria, to assemble Metagenome-assembled Genomes (MAGs). We obtained a total of 16 bacterial genomes, 15 of these enriched in the smallest fraction of the gradient. According to the recently proposed Genome Taxonomy Database (GTDB) taxonomy, these MAGs belong to Bacteroidota, Firmicutes_A, Firmicutes, Proteobacteria and Spirochaetota phyla. Fifteen MAGs were novel at the species level, and four at the genus level. The functional characterization of these MAGs suggests differences from what is currently known from the genomic potential of well-characterized members from this complex environment. Species of the phyla Bacteroidota and Spirochaetota show the potential for hydrolysis of complex polysaccharides in the plant cell wall and towards the production of B-complex vitamins and protein degradation in the rumen. Conversely, the MAGs belonging to Firmicutes and Alphaproteobacteria, showed a reduction in several metabolic pathways, however, they have genes for lactate fermentation and the presence of hydrolases and esterases related to chitin degradation. Our results demonstrate that the separation of the rumen microbial community by size and density reduced the complexity of the ruminal fluid sample and enriched some poorly characterized ruminal bacteria allowing exploration of their genomic potential and their functional role in the rumen ecosystem.